2019
DOI: 10.1155/2019/6051262
|View full text |Cite
|
Sign up to set email alerts
|

Higd1a Protects Cells from Lipotoxicity under High-Fat Exposure

Abstract: Hypoxia-inducible gene domain family member 1A (Higd1a) has recently been reported to protect cells from hypoxia by helping to maintain normal mitochondrial function. The potential induction of Higd1a under high-fat exposure and whether it could protect cells from oxidative stress attracted our attention. Initially, 0.4 mM oleic acid and 0.2 mM palmitate were added to the growth media of HepG2 and LO2 cells for 72 hours. We discovered increased Higd1a expression, and knocking down Higd1a impaired mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Moreover, Myr upregulated the p53-inducible protein 1 ( TP53INP1 ) gene, which also promotes autophagy by interacting with autophagy-related protein family (ATG) [ 48 ]. The expression of SNX14, involved in the regulation of autophagy and lipid metabolism, was significantly increased by Myr [ 49 , 50 ], as well as that of hypoxia inducible gene 1 ( HIGD1A ), involved in oxidative stress and lipotoxicity protection [ 51 ]. At the same time, Myr downregulated ACACA, the rate-limiting enzyme regulating de novo fatty acid synthesis, whose increased activity has been associated with inflammation and CFTR deficiency [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Myr upregulated the p53-inducible protein 1 ( TP53INP1 ) gene, which also promotes autophagy by interacting with autophagy-related protein family (ATG) [ 48 ]. The expression of SNX14, involved in the regulation of autophagy and lipid metabolism, was significantly increased by Myr [ 49 , 50 ], as well as that of hypoxia inducible gene 1 ( HIGD1A ), involved in oxidative stress and lipotoxicity protection [ 51 ]. At the same time, Myr downregulated ACACA, the rate-limiting enzyme regulating de novo fatty acid synthesis, whose increased activity has been associated with inflammation and CFTR deficiency [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its gene product was recently reported to protect cells from hypoxia and from lipotoxicity related to fat oxidation impairment. Indeed, HIGD1a decreases oxygen radical production, helping to maintain a normal mitochondrial function [ 51 ]. A reduced autophagy paired with lipid accumulation because of decreased oxidation rate was already observed in CF cells and rescued by Myr [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIGD-1A is induced by hypoxia in a HIF-1-dependent manner. Similarly, ROS accumulation in HepG2 cells promotes HIGD-1A expression levels by upregulating HIF-1α and PGC-1α expression levels under high-fat exposure (39). HIGD-1A inhibits the pERK/p27KIP1/retinoblastoma protein signaling pathway, which leads to cell cycle arrest (40).…”
Section: Discussionmentioning
confidence: 96%
“…The HIGD1A protein of mammals is related to Rcf1 and Rcf2 of yeast (7). Using fluorescence microscopy, Li et al (40) have shown that knockdown of human HIGD1A in cultured cells lowers mitochondrial membrane potential, whereas overexpression of HIGD1A protects.…”
Section: Discussionmentioning
confidence: 99%